2014
DOI: 10.1179/2151090314y.0000000007
|View full text |Cite
|
Sign up to set email alerts
|

One-leg standing time with eyes open: comparison between the mouth-opened and mouth-closed conditions

Abstract: The vertical mandibular position may affect body balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…For example, 1 study reported that OLST times were significantly shorter when participants had their mouths open than when they were closed. [23] Participants in our study were not specifically instructed to have their mouth open or closed during OLST. Therefore, there may have been a large error in the measurement of OLST.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 1 study reported that OLST times were significantly shorter when participants had their mouths open than when they were closed. [23] Participants in our study were not specifically instructed to have their mouth open or closed during OLST. Therefore, there may have been a large error in the measurement of OLST.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have examined the association between oral function and physical function from the perspective of long-term care prevention [4]. Many reports have focused on oral conditions, such as the number of teeth and occlusal support [5][6][7]. In recent years, several reports have highlighted the muscle strength of oral and physical functions, such as tongue pressure and grip strength [8], occlusal force and grip strength [9], and occlusal force and lower limb muscle strength [10].…”
Section: Introductionmentioning
confidence: 99%